Droplet microfluidics for microbiology: techniques, applications and challenges. Issue 12 (23rd May 2016) - Kaminski, Tomasz S.; Scheler, Ott; Garstecki, Piotr
Abstract : Droplet microfluidics has rapidly emerged as one of the key technologies opening up new experimental possibilities in microbiology. Abstract : Droplet microfluidics has rapidly emerged as one of the key technologies opening up new experimental possibilities in microbiology. The ability to generate, manipulate and monitor droplets carrying single cells or small populations of bacteria in a highly parallel and high throughput manner creates new approaches for solving problems in diagnostics and for research on bacterial evolution. This review presents applications of droplet microfluidics in various fields of microbiology: i) detection and identification of pathogens, ii) antibiotic susceptibility testing, iii) studies of microbial physiology and iv) biotechnological selection and improvement of strains. We also list the challenges in the dynamically developing field and new potential uses of droplets in microbiology.